Extending transformation. (Transformative Works & Cultures, 2009)
The article discusses various reports published within the issue, including one by Debora J. Halbert on the gendered and fannish investment aspect in copyright industry, an essay by Jason Mittell and Leora Hadas on growing fandom and online network, and one by Avi Santo on the role of online publishing for academic scholars.